2015
DOI: 10.1093/jxb/erv137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of stilbene metabolism in Vitis sylvestris

Abstract: HighlightWe show that the ancestor of cultivated grapevine harbours genetic factors that increase the inducibility of stilbenes correlated with increased resistance to the important pathogen grapevine downy mildew.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 43 publications
5
86
0
1
Order By: Relevance
“…Viniferin is highly toxic and can be considered an important marker for grapevine resistance to downy mildew (Pezet et al, 2004), but very little information is available on the role of constitutive stilbenoids (Duan et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Viniferin is highly toxic and can be considered an important marker for grapevine resistance to downy mildew (Pezet et al, 2004), but very little information is available on the role of constitutive stilbenoids (Duan et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…A1). In a previous study (Duan et al 2015), we identified considerable variation in stilbene inducibility among grapevine (Vitis) genotypes, and reported differences in their abundance and profiles in response to UV-C pulsing. The V. sylvestris genotypes Hoe29, Ke53 and Ke83 and the V. vinifera cultivar Pinot Blanc were found to develop elevated stilbene levels in response to UV light, with high stilbene accumulation, and were classified as high-stilbene types, with the most notable representatives being Hoe29 and Ke53.…”
Section: Introductionmentioning
confidence: 91%
“…sylvestris genotypes 'Hoe29', 'Ke53' and 'Ke83', and the V. vinifera cultivars 'Augster Weiss', 'Pinot Blanc', and 'Müller-Thurgau', are maintained as living specimens in the grapevine collection of the Botanical Garden of the Karlsruhe Institute of Technology, Germany (Olmo 1976, Ledesma-Krist et al 2014). The V. sylvestris genotypes Hoe29, Ke53 and Ke83 and the V. vinifera cultivar Pinot Blanc were classified as high-stilbene types, while two V. vinifera cultivars, Augster Weiss and Müller-Thurgau have been categorized as low-stilbene types in response to UV light (Duan et al 2015). For the analysis in this study, entire leaves of a similar age (based on node size and position), were harvested from greenhouse-grown plants cultivated at a temperature of 22°C and 18°C (day and night, respectively) and a photoperiod of 14 h light and 10 h dark.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations